Competitive energy consumption under transmission constraints in a multi-supplier power grid system. Issue 5 (4th April 2017) - Popov, Ivan; Krylatov, Alexander; Zakharov, Victor; Ivanov, Dmitry
ABSTRACT: Power grid architectures need to be revised in order to manage the increasing number of producers and, more generally, the decentralisation of energy production and distribution. In this work, we describe a multi-supplier multi-consumer congestion model of a power grid, where the costs of consumers depend on the congestion in nodes and arcs of the power supply network. The consumer goal is both to meet their energy demand and to minimise the costs. We show that the methods of non-atomic routing can be applied in this model in order to describe current distribution in the network. We formulate a consumer cost minimisation game for this setting, and discuss the challenges arising in equilibrium search for this game.